2004
DOI: 10.1111/j.1440-1819.2003.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity and gender differences of persons incarcerated for methamphetamine abuse in Taiwan

Abstract: Methamphetamine (MAP) abuse has been common in Taiwan for the past decade. The purpose of the present study was to investigate MAP abuse in Taiwan, with specific attention to psychiatric comorbidity and gender differences. A total of 325 MAP abuse subjects (180 male, 145 female) from a detention center in Taipei were assessed with the Diagnostic Interview for Genetic Studies.The following were studied: drug use behavior, treatment-seeking behavior, lifetime prevalence of mood disorders, MAP psychosis, alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
62
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 28 publications
(35 reference statements)
14
62
4
Order By: Relevance
“…Around 60% of methamphetamine users and 76% of heroin users in the present study had criminal records other than drug crimes. These rates of criminal records were generally higher than those reported in previous studies 16,17 in Taiwan. Lin et al 17 reported that 45.2% of incarcerated male methamphetamine users had criminal records other than illicit drug use.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Around 60% of methamphetamine users and 76% of heroin users in the present study had criminal records other than drug crimes. These rates of criminal records were generally higher than those reported in previous studies 16,17 in Taiwan. Lin et al 17 reported that 45.2% of incarcerated male methamphetamine users had criminal records other than illicit drug use.…”
Section: Discussioncontrasting
confidence: 54%
“…These rates of criminal records were generally higher than those reported in previous studies 16,17 in Taiwan. Lin et al 17 reported that 45.2% of incarcerated male methamphetamine users had criminal records other than illicit drug use. Their study used subjects' reports as the only information resources, and might underestimate crime rates due to prevarication.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…MAMP users place the powder of MAMP in empty light bulbs or glass bottles and heat these containers to inhale the smoke. As MAMP is a stimulant that acts on the central nervous system, misuse can have serious physical, psychological, and social consequences (Weaver and Schnoll, 1999), including MAMP psychosis (Lin et al, 2004). Until now, little is known about the prevalence of suicidal ideation and its correlates in adolescent MAMP use.…”
mentioning
confidence: 98%
“…Taiwanese adults in detention with amphetamine abuse found less than 1% also used cannabis (Lin et al, 2004). In a Japanese cohort, less than half of injecting stimulant users had a lifetime history of cannabis use (Matsumoto et al, 2002).…”
Section: The Overlap Between Cannabis and Stimulant Use Disordersmentioning
confidence: 99%